Personal Selling Strategy - Dede Suleman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
For a seller, the ability that needs to be improved is how to make sales because this is the key to success in this profession. This material is made so that participants can understand it regarding Personal sales, which is the main basis for marketing. A comprehensive understanding of Personal selling is essential for marketing and business students. This not only provides practical insight into the sales process in the field, but also allows students to combine theoretical concepts with real-world applications. You will understand how marketing strategies are designed to achieve specific market goals and how Personal selling can be a highly effective element in achieving those goals. Additionally, in Personal selling , you will learn the importance of building long-term relationships with your customers. It's not just about selling products, but about building and maintaining strong relationships with customers. This understanding is invaluable in an era when customer loyalty is the key to business success. Therefore, Personal selling is not just a theoretical subject in the curriculum, but is also a bridge to the real business world, providing valuable insights and skills that can be applied to a variety of careers in the marketing and corporate sectors.